Tracing the links between Womanhood, Enslavement and Madness in Jean Rhys’s Wide Sargasso Sea: A Feministic Study - Mahmood, Ambreen; Nisa, Mehr un; Manzoor, Amna (Annals of Human and Social Sciences, 2024)
This paper attempts to discover the linkage between womanhood, enslavement and madness in Jean Rhys’s novel Wide Sargasso Sea. The role of various social factors like patriarchal oppression, physical confinement and financial dependence in pushing the female characters towards ultimate madness, has been focused in the present study. The study is unique in the sense that along with close analysis of the structure of language, it probes into the textual discourse of the novel as well to find out the undercurrents contributing in the ultimate madness of the female characters in the novel. So far as the theoretical framework is concerned, it is drawn initially by defining the arena of Gender Studies illustrating the terms ‘Womanhood’ and ‘Madness’ as taken up by feminist theorists under the notions of patriarchal tyranny, social confinement and ultimate madness of females. The study is predominantly qualitative in nature as the data is based on the text of the novel. To achieve the targeted objectives of the study, textual analysis is selected as technique for data analysis. The findings bring forth the causal linkage that is present inherently between womanhood, enslavement and madness.